Germany : VET in Europe - 2016 country report - Hippach-Schneider, Ute [Verfasser]; Huismann, Adrienne [Verfasser] (Bundesinstitut für Berufsbildung, 2017)
"This report is an overview of the vocational education and training (VET) system in Germany. Information is presented according to the following themes: 1. External factors influencing VET; 2. Providing VET in a lifelong learning perspective; 3. Shaping VET qualifications; 4. Promoting participation in VET. This overview was prepared in 2016 and its reference year is 2015 or, if not available, 2014." (Editor, BIBB-Doku)
Keywords: S System beruflicher Bildung; S 1.3 Berufliche Erstausbildung; S 2.3 Berufsbildungspolitik; S 1.5.2 Berufliche Weiterbildung; S 4.1 Finanzierungsquellen; I 2.1 Deutschland; Berufsbildungssystem; Berufsbildungspolitik; Berufsausbildung; Berufliche Weiterbildung; Bildungsfinanzierung; Bundesrepublik Deutschland